Combining visual and acoustic features for music genre classification. (1st March 2016) - Nanni, Loris; Costa, Yandre M.G.; Lumini, Alessandra; Kim, Moo Young; Baek, Seung Ryul
Highlights: Coupling texture descriptors and acoustic features. Bag of feature approach can be effectively used in this problem. Heterogeneous ensemble of different classifiers improves performance. Abstract: Since musical genre is one of the most common ways used by people for managing digital music databases, music genre recognition is a crucial task, deep studied by the Music Information Retrieval (MIR) research community since 2002. In this work we present a novel and effective approach for automated musical genre recognition based on the fusion of different set of features. Both acoustic and visual features are considered, evaluated, compared and fused in a final ensemble which show classification accuracy comparable or even better than other state-of-the-art approaches. The visual features are locally extracted from sub-windows of the spectrogram taken by Mel scale zoning: the input signal is represented by its spectrogram which is divided in sub-windows in order to extract local features; feature extraction is performed by calculating texture descriptors and bag of features projections from each sub-window; the final decision is taken using an ensemble of SVM classifiers. In this work we show for the first time that a bag of feature approach can be effective in this problem. As the acoustic features are concerned, we propose an ensemble of heterogeneous classifiers for maximizing the performance that could be obtained starting from the acoustic features. First timbre features are obtained from the audio signal, second some statistical measures are calculated from the texture window and the modulation spectrum, third a feature selection is executed to increase the recognition performance and decrease the computational complexity. Finally, the resulting descriptors are classified by fusing the scores of heterogeneous classifiers (SVM and Random subspace of AdaBoost). The experimental evaluation is performed on three well-known databases: the Latin Music Database (LMD), the ISMIR 2004 database and the GTZAN genre collection. The reported performance of the proposed approach is very encouraging, since they outperform other state-of-the-art approaches, without any ad hoc parameter optimization (i.e. using the same ensemble of classifiers and parameters setting in all the three datasets). The advantage of using both visual and audio features is also proved by means of Q -statistics, which confirms that the two sets of features are partially independent and they are suitable to be fused together in a heterogeneous system. The MATLAB code of the ensemble of classifiers and for the visual features extraction will be publicly available (see footnote 1) to other researchers for future comparisons. The code for acoustic features is not available since it is used in a commercial system.